Anti-GluK2 antibody-positive autoimmune encephalitis concurrent with multiple myeloma: a case report - Zhengping Cheng; Yang Song; Shuqi Zhao; Xiaowen Sui; Lili Xie; Hongling Zhao; Xin Pan; Li Cui; Xinran Huang; Shubei Ma (BMC Neurology)
Abstract Background Autoimmune encephalitis associated with anti-GluK2 antibodies is a recently identified condition, typically characterized by cerebellar ataxia. This case report presents a unique clinical manifestation involving involuntary movements and emotional dysregulation, expanding the known phenotype spectrum. Case presentation A 60-year-old woman presented with a two-year history of involuntary movements predominantly affecting her lower limbs and facial muscles, occasionally accompanied by hysterical shouting. Initial investigations revealed coexisting multiple myeloma (MM) and anti-GluK2 antibody positivity. Following MM-specific therapy, including bortezomib, cyclophosphamide, and dexamethasone, the patient's symptoms resolved, and her serum anti-GluK2 antibody titers decreased significantly. Conclusions This case suggests that involuntary movements and psychiatric symptoms may represent novel phenotypes of anti-GluK2 antibody-associated autoimmune encephalitis. The findings underscore the importance of recognizing the diverse clinical presentations of this rare condition and prompt further research into its underlying mechanisms.